ILLEGAL ENTREPRENEUR: NECESSITY BASE ENTREPRENEUR OR OPPORTUNITY BASE ENTREPRENEUR (Exploratory Study of Illegal Entrepreneurship in Padang City) - Riko Putra; Hafiz Rahman; Alfitman (Journal Publicuho, 2024)
The development of business opportunities and life demands have led many entrepreneurs to operate illegally, including those in Padang City, West Sumatra. This study aims to understand the motivations behind illegal entrepreneurs in Padang City, West Sumatra, for starting their businesses. The research employs a qualitative method using thematic analysis with NVivo 12 Plus software for data processing. The findings reveal that the motivations for illegal entrepreneurship in Padang City are driven partly by necessity (Necessity-Based Entrepreneur) and partly by the recognition of business opportunities (Opportunity-Based Entrepreneur). Necessity-based illegal entrepreneurship is observed in the sand mining sector and the counterfeit products sector. Conversely, opportunity-based entrepreneurship is identified in the thrifting sector and also in the counterfeit products sector. Additionally, the study finds that some illegal entrepreneurs are driven by personal interests or comfort, particularly in the thrifting and sand mining sectors. Generally, illegal businesses in Padang City operate without permits and do not pay taxes. A portion of these entrepreneurs are unaware of the legal consequences of their activities, while others are cognizant of the potential repercussions of engaging in illegal businesses.